“Más parecen disparates que sentencias”: on the Comic Tale and Censorship in the Golden Age Drama (Castilla. Estudios de Literatura, 2011)
The drama of the Golden Age is an example of high literature closely linked to the oral tradition, and is one of the genres probably most open to the use of traditional and folkloric elements: fairy-tales, proverbs, songs, ballads, nursery rhymes, spells, etc. In composing their works, Spanish playwrights exploited this source both deeply and widely. One method of embedding these traditional elements, frequently met with in works of this period, is the threading of narrative beads. This narrative bead-threading generally has a comic function, and it is the investigation of this function, within the narrow bounds that official censorship allowed, that this article focuses upon.